Double methylation of tRNA-U54 to 2′-O-methylthymidine (Tm) synergistically decreases immune response by Toll-like receptor 7. Issue 18 (8th August 2018) - Keller, Patrick; Freund, Isabel; Marchand, Virginie; Bec, Guillaume; Huang, Raven; Motorin, Yuri; Eigenbrod, Tatjana; Dalpke, Alexander; Helm, Mark
Abstract: Sensing of nucleic acids for molecular discrimination between self and non-self is a challenging task for the innate immune system. RNA acts as a potent stimulus for pattern recognition receptors including in particular human Toll-like receptor 7 (TLR7). Certain RNA modifications limit potentially harmful self-recognition of endogenous RNA. Previous studies had identified the 2′-O-methylation of guanosine 18 (Gm18) within tRNAs as an antagonist of TLR7 leading to an impaired immune response. However, human tRNA Lys 3 was non-stimulatory despite lacking Gm18. To identify the underlying molecular principle, interferon responses of human peripheral blood mononuclear cells to differentially modified tRNA Lys 3 were determined. The investigation of synthetic modivariants allowed attributing a significant part of the immunosilencing effect to the 2′-O-methylthymidine (m 5 Um) modification at position 54. The effect was contingent upon the synergistic presence of both methyl groups at positions C5 and 2'O, as shown by the fact that neither Um54 nor m 5 U54 produced any effect alone. Testing permutations of the nucleobase at ribose-methylated position 54 suggested that the extent of silencing and antagonism of the TLR7 response was governed by hydrogen patterns and lipophilic interactions of the nucleobase. The results identify a new immune-modulatory endogenous RNA modification that limits TLR7 activation by RNA.